Safety of Improved Milbond-TX® Mycotoxin Binder When Fed to Broiler Breeders above Recommended Levels - Schlumbohm, M.J.; Kriseldi, R.; England, J.A.; Coon , C.N. (International Journal of Poultry Science, 2014)
A continual concern in poultry nutrition is the negative effects that mycotoxins have on animal performance when contaminated grain is used as a dietary ingredient. Mycotoxin binders have been available for decades and are used in the feed as an effective approach to decreasing the intestinal absorption of several mycotoxins, especially when present in low dietary concentrations. The research reported herein with broiler breeders was conducted to test the safety of an effective mycotoxin binder, Improved Milbond-TX® (IMTX), when added to the diet in concentrations higher than the 0.25% which is recommended by the manufacturer. Beginning at 21 weeks of age a typical corn-soybean meal diet was supplemented with IMTX at concentrations of 0, 0.5 and 1.0%. These three dietary treatments were fed continuously from 21 to 35 weeks of age to 300 broiler breeder hens. Data were collected on egg production, egg weights, hatchability, fertility and chick weights from 24 to 35 weeks of age. Egg production, expressed as eggs per hen housed, was not significantly different (p>0.05) among the three dietary treatments. Also, no significant differences (p>0.05) were found among the dietary treatments for egg weights, hatchability, fertility and chick weights. Results from this study show that an accidental over-supplementation of a broiler breeder diet resulting in up to 4 times the recommended dietary concentration of IMTX is not expected to result in any negative effect on broiler breeder performance or of the weight of chicks at hatch.